Integrated Microwave Photonics: A Multifunctional Photonic Integrated Circuit for Diverse Microwave Signal Generation, Transmission, and Processing (Laser Photonics Rev. 13(6)/2019). Issue 6 (14th June 2019) - Zou, Xihua; Zou, Fang; Cao, Zizheng; Lu, Bing; Yan, Xianglei; Yu, Ge; Deng, Xiong; Luo, Bin; Yan, Lianshan; Pan, Wei; Yao, Jianping; Koonen, Antonius M. J.
Abstract : In article number1800240, Xihua Zou, Zizheng Cao, Wei Pan, Jianping Yao, Antonius M. J. Koonen, and co‐workers develop a versatile and powerful integrated circuit of microwave photonics, which enables seven fundamental functions across microwave signal generation, transmission, and processing. Particularly, this photonic circuit is demonstrated for direct deployment in real‐world applications, e.g., high‐speed railways and broadband wireless communications, accelerating fundamental research from the laboratory to daily life.